First results of the radon concentration monitoring in Abaliget and Kispaplika Caves - Koltai Gabriella (Acta climatologica, 2014)
Radon concentration has been investigated in Abaliget and Kispaplika caves, Mecsek Mountains, Hungary for 9 month. Track-etched detectors were used to measure the radon levels of cave air inside the passages. Our primary aim was to gain information about both the radon concentration levels and the convectional characteristics of these caves. Meteorological data provided by the Public Limited Company for Radioactive Waste Management was used to analyse the possible direction of airflow inside the caves. Both caves were characterized by higher summer and lower winter values and the changes of radon concentration were governed by the inside and outside temperature difference induced ventilation of the caves.